Teacher's efforts in improving students' Islamic behavior: Akidah Akhlak - Derr Xin; Weng Martin; Wang Lita (International Journal of Educational Narratives, 2023)
Background. This study used the descriptive qualitative method. Researchers collected data by using in-depth interviews, participant observation, and documentation. Purpose. This study aims to determine the efforts of moral aqidah teachers in improving students' Islamic behavior, know the obstacles of moral aqidah teachers in enhancing students' Islamic behavior, and how to find out how to overcome the challenges of moral aqidah teachers in improving students' Islamic behavior. Method. While the data analysis technique used interactive analysis, with the stages of data collection, data editing, and data presentation. Results. The results of this study: 1) that the efforts of the aqidah moral teacher in improving the Islamic behavior of students by holding religious activities such as holding regular monthly recitations, increasing students' awareness by living clean, setting good examples, providing classical guidance; 2) Obstacles in improving the Islamic behavior of students from environmental factors, and parents; 3) how to overcome obstacles in improving the Islamic behavior of students by giving punishment and collaborating with boarding school administrators and parents of students. Conclusion. It was proveb by the calculation of N-gain of 0,76 with category